2013
DOI: 10.1039/c3dt33097d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of divalent metal ions from aqueous solutions using graphene oxide

Abstract: The adsorptive properties of graphene oxide (GO) towards divalent metal ions (copper, zinc, cadmium and lead) were investigated. GO prepared through the oxidation of graphite using potassium dichromate was characterized by scanning electron microscopy (SEM), powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and infrared spectroscopy (FT-IR). The results of batch experiments and measurements by flame atomic absorption spectrometry (F-AAS) indicate that maximum adsorption can be achieved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
390
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 753 publications
(448 citation statements)
references
References 55 publications
(79 reference statements)
29
390
2
Order By: Relevance
“…From the kinetic equation, Q e and k were calculated to be 200.4 mg g −1 and 0.231 g mg −1 min −1 , respectively. Previous studies reported pseudo‐second‐order kinetic models for the adsorption of U(VI) by other materials such as GOs,27 amidoximated magnetite/GO composites,28 FeS,29 and melamine‐modified graphene hydrogels 30. The values of k were much higher than those previous references, which confirmed the significant adsorption efficiency of the NPS‐GLCs.…”
Section: Resultsmentioning
confidence: 99%
“…From the kinetic equation, Q e and k were calculated to be 200.4 mg g −1 and 0.231 g mg −1 min −1 , respectively. Previous studies reported pseudo‐second‐order kinetic models for the adsorption of U(VI) by other materials such as GOs,27 amidoximated magnetite/GO composites,28 FeS,29 and melamine‐modified graphene hydrogels 30. The values of k were much higher than those previous references, which confirmed the significant adsorption efficiency of the NPS‐GLCs.…”
Section: Resultsmentioning
confidence: 99%
“…The functional groups of GO are capable of forming hydrogen bonds or electrostatic interactions with aromatics and polar compounds or metal ions [ 18,19,20 ]. GO has proved to be an ideal sorbent for SPE [ 21 ] and SPME [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The removal rate of Pb 2+ by CHR600 was 97.5% at C 0 of 100 mg/L, significantly greater than that by CHR300 (88.6%), implying that the higher sorption affinity of Pb 2+ onto the biochar produced at high temperature. It [8] and graphene oxide (GO) [9]. The surface oxygen-containing functional groups in these carbonaceous material plays a significant role in the adsorption process of the metal ions by an electrostatic attraction or complexation.…”
Section: Pb 2+ and CD 2+ Removal By Biocharsmentioning
confidence: 99%